Research on Total Water Consumption Management under Rigid Constraint of Water Resources in Southern China with Abundant Water Resources —— A Case Study of Pearl River Basin - LIU Yanju; YANG Ruixiang (Renmin Zhujiang)
Taking water resources as the maximum rigid constraint has become an inevitable requirement for promoting unified management of water resources and high-quality development of the economy and society in the new situation.The core meaning of the maximum rigid constraint of water resources is to use water resources as their capacity permits.Total water consumption control management is the core standard to implement the rigid constraint of water resources.Based on the characteristics of water resources in the Pearl River Basin with better natural water resources conditions,this study focuses on solving the existing practical problems in the implementation of the rigid constraint system of water resources in the Pearl River Basin,such as weak foundation,poor system and mechanism,and imperfect management of total water consumption indicators.The study also puts forward suggestions on total water consumption management indicators of the basin based on available water resources and the sum of water transferred in and out.The scope of application and the preconditions for dynamic adjustment of total water consumption management indicators are clarified,and the indicator adjustment mode is established.It provides support for strengthening the management of total water consumption in the Pearl River Basin under the background of the rigid constraint of water resources,vitalizes the total water consumption indicators,and improves utilization efficiency.